KOMPARASI WORKING MEMORY MUSISI DAN NON MUSISI: SEBUAH TINJAUAN PUSTAKA - Damar Sari, Ni Made Bintang; Susilawati, Luh Kadek Pande Ary (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
ABSTRACT Introduction: Working memory is one of the three components of executive function which has four components, namely central executive, phonological loop, visuospatial sketchpad, and episodic buffer. Many studies examining working memory in musicians and non-musicians have found that working memory performance in musicians outperforms non-musicians. Discussion: Working memory has three components which each have a role in the activities carried out by the individual. Apart from that, working memory is also sensitive to various factors, one of which is musical training. Music training is considered to influence working memory and can have a positive impact on working memory abilities. The influence of musical training then results in differences in the performance of working memory in musicians when compared to non-musicians. Conclusion: Working memory advantages have not been consistently found in every study comparing musicians and non-musicians. However, in general, the research results show that musicians have superior working memory performance compared to non-musicians. This can be caused by musical training factors and the diversity of musicians' excellence can be caused by differences in musical training.   Keywords: Working memory, Music Training, Musicians, Non-Musicians